2001
DOI: 10.1159/000051637
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Overexpression and Genetic Aberrations in Metastatic Squamous-Cell Carcinoma of the Skin

Abstract: Background: Cutaneous squamous-cell carcinoma (SCC) sometimes causes lymph node metastasis and results in poor prognosis. However, little is known about cytogenetic alterations underlying tumor progression or metastasis. The aim of the present study was to investigate the genetic aberrations and expression of epidermal growth factor receptor (EGFR) in metastatic SCC of the skin. Methods: We undertook comparative genomic hybridization (CGH) analysis of 4 specimens which were obtained from a case of cutaneous SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(77 citation statements)
references
References 5 publications
4
71
2
Order By: Relevance
“…1,5 This suggests that other mechanisms of Ras activation play a role in the human disease. For example, epidermal growth factor receptor overexpression by amplification is known to occur in human SCC, 6,7 and epidermal growth factor receptor could lead to the biochemical stimulation of Ras. In animal models, overexpression of epidermal growth factor receptor ligands like transforming growth factor-␣, 8 or a dominant form of the Ras exchange factor Sos of seven less (SOS), 9 act as an initiation event in the epidermis, further demonstrating that alterations in Ras upstream signals could lead to tumorigenesis in the skin via wildtype Ras activation.…”
Section: Models Of Epidermal Carcinogenesis Have Demonstrated That Ramentioning
confidence: 99%
“…1,5 This suggests that other mechanisms of Ras activation play a role in the human disease. For example, epidermal growth factor receptor overexpression by amplification is known to occur in human SCC, 6,7 and epidermal growth factor receptor could lead to the biochemical stimulation of Ras. In animal models, overexpression of epidermal growth factor receptor ligands like transforming growth factor-␣, 8 or a dominant form of the Ras exchange factor Sos of seven less (SOS), 9 act as an initiation event in the epidermis, further demonstrating that alterations in Ras upstream signals could lead to tumorigenesis in the skin via wildtype Ras activation.…”
Section: Models Of Epidermal Carcinogenesis Have Demonstrated That Ramentioning
confidence: 99%
“…48 Relative expression of these receptors in tumor cells versus adjacent epidermis was not addressed in that study, which used bulk tumor specimens. In cutaneous SCC, studies have reported variable levels of ErbB1 and ErbB2 in primary tumors but increased expression of ErbB1 47 and ErbB2 46 proteins in metastatic lesions.…”
mentioning
confidence: 99%
“…85 Targeted therapies and forms of immunotherapy utilize the overexpression of epidermal growth factor receptor (EGFR) in the setting of cSCC to disrupt cell proliferation. [86][87][88] These novel treatments, which include monoclonal antibodies, such as cetuximab, can offer an overall disease control rate of 69%, as seen in a phase II trial using cetuximab in the setting of metastatic cSCC. 88 A further stage III randomized trial adding cetuximab to cisplatin significantly improved treatment response when compared with placebo (26.3 vs 9.8%; p=0.29).…”
Section: Novel Treatmentsmentioning
confidence: 99%